Correlation Analysis of Seci-Based Discharge Planning Implementation with Patient Satisfaction - Musrini, Amirul; Ibnu, Faisal; Hidayati, Rina Nur; Zamroni, Asroful Hulam (GLOBAL HEALTH SCIENCE GROUP, 2024)
Discharge planning has been implemented and provided by nurses in all hospitals, but patients still feel dissatisfied regarding the response and explanation in nursing care. Therefore, this study aims to analyze the correlation of SECI-based discharge planning with patient satisfaction in hospitals. This study used a cross-section design with a sample of 50 patients in Palem Room 1 RSUD Dr. Soetomo. This research used a consecutive sampling technique for one month. Research data was collected through a discharge planning implementation questionnaire with a valid test of <0.5 and a reliable test of 0.780 >0.6, as well as a patient satisfaction questionnaire with a valid test of 0.5 and a reliable test of 0.844 >0.6. Research data was processed using the description test and the Spearman rho test with a p-value ≤ 0.05. There is a relationship between charge planning and patient satisfaction (0.000). In charge of planning for the patient, the nurse can provide information and actions according to the patient's expectations so that the level of independence of the patient and family can be optimal. Implementation of existing discharge planning is maintained and improved and provided to all patients starting from the time the patient enters the treatment room until the day the patient returns. Nurses provide discharge planning services to improve and maintain all indicators of socialization, externalization, combination, and internalization.